Amelioration of Alcohol Induced Gastric Ulcers Through the Administration of Lactobacillus plantarum APSulloc 331261 Isolated From Green Tea - Park, Haryung; Cho, Donghyun; Huang, Eunchong; Seo, Ju Yeon; Kim, Wan Gi; Todorov, Svetoslav Dimitrov; Ji, Yosep; Holzapfel, Wilhelm Heinrich (Frontiers in Microbiology, 2020)
Gastric inflammation is an indication of gastric ulcers and possible other underlying gastric malignancies. Epidemiological studies have revealed that many Asian countries, including South Korea, suffer from a high incidence of gastric diseases derived from high levels of stress, alcoholic consumption, pyloric infection and usage of nonsteroidal anti-inflammatory drugs (NSAIDs). Clinical treatments of gastric ulcers are generally limited to proton pump inhibitors that neutralize the stomach acid, and application of antibiotics for Helicobacter pylori eradication, both of which are known to have a negative effect on the gut microbiota. The potential of probiotics for alleviating gastrointestinal diseases such as intestinal bowel syndrome and intestinal bowel disease receives increasing scientific interest. Probiotics may support the amelioration of disease-related symptoms through modulating the gut microbiota without causing dysbiosis. In this study the potential of Lactobacillus plantarum APSulloc 331261, isolated from green tea, for alleviating gastric inflammation was investigated in an alcohol induced gastric ulcer murine model. Treatment with the test strain significantly influenced the expression of pro-inflammatory and anti-inflammatory biomarkers such as interleukin 6 and interleukin 10, respectively, as was also indicated by less severe gastric morphological changes and the histological score of the gastric tissues. A significant increase in the abundance of Akkermansia within the Lb. plantarum APSulloc 331261 treated group compared to the ethanol induced control group also correlated with a decrease in the ratio of acetate over propionate. The increased levels of propionate in the Lb. plantarum APSulloc 331261 group appear to result from the impact of the test strain on the microbial population and the resulting metabolic activities. Moreover, there was a significant increase in beta-diversity in the group that received the Lb. plantarum APSulloc 331261 over that of the alcohol induced control group.